Integrating Scientific Research: Theory and Design of Discovering Similar Constructs - Endicott, James; Larsen, Kai R.; Lukyanenko, Roman; Bong, Chih How (2017)
Assessing the similarity of proposed theoretical constructs to each other and those previously known and studied is imperative in theoretical research. In this paper we turn to theories of similarity judgement from cognitive psychology for the understanding of the process of establishing similarity between one or more constructs. Then, guided by these theories, we develop an integrated method for automatic detection of similar constructs. We apply the method to constructs from leading IS journals, a major journal in psychology, and the interdisciplinary overlap between the IS and psychology constructs. Our paper contributes to methodology of research, design science research, behavioral IS research, text mining and information retrieval theory and practice, IS research on ontology alignment and schema matching as well as cognitive theories of similarity in psychology